Antifeeding effect of some plant extracts on tobacco cutwormSpodoptera litura (Lepidoptera: Noctuidae) (NTU Journal of Agriculture and Veterinary Science, 2024)
A study was conducted to test the anti-nutritional effect of ethanolic extracts of Nerium oleander, Melia azedarach, Mentha arvensis , and Ocimum basilicum plants on fifth-instar larvae of the tobacco cutworm Spodoptera litura, where N. oleander, M. azedarach, plants showed activity in preventing larval feeding. The results showed that the extract of  N.oleander leaves, M azedarach leaves, and fruits was significantly superior to M. arvensis and O. basilicum leaves in all tested criteria. The values of the nutrition prevention factor reached (55.5, 51.4, 51.3, 16.9, and 10.9%), respectively, while the values of the leaf protection rate reached (59.7, 57.3, 59.3, 25.7, and 20.6%) , respectively. This variation in anti-nutritional activity may be due to the variation in the types and concentrations of the active alkaloid and phenolic compounds revealed by chemical analysis. The statistical analysis showed that there was a positive and significant correlation between the nutritional intake factor and the alkaloid compounds Atropine and Xanthine, whose values reached( 0.943 and 0.947), respectively, and a significant correlation with the two phenolic compounds, Galic acid and Rutine, whose values reached (0.860 and 0.864), respectively. Hence, it can be said that N.oleander , M azedarach plants can be alternative materials to pesticides in pest management programs that rely on compounds that are safe for the environment and human health.